Socialization And Education Of The Impact Of Free Association On High School Students Of Posigadan Village Milangodaa Kec. Tomini Kab. South Mongondow Bolaang North Sulawesi Province - Leni Dwi Nurmala; Yusrianto Kadir; Nurwita Ismail; Roy Marten Moonty; Aldiyanto A. Sabuati; Wahyu Muhaimain Abdullah; Aldi Syahrian; Agung Cahyo Hasan; Nova Laupode; Desri Landa Singal; Indrawan I. Laria; Fitriyani Supu; Yasril S. Hamzah; Salma Kumai (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Free promiscuity has now become one of the behaviors that is very concerning. One of the negative impacts caused by adolescent behavior is pregnancy outside of marriage. Community service carried out by students as a form of implementation of the Tri Dharma of Higher Education carried out by the University of Gorontalo in the form of Community Service Lectures (KKP) which aims to contribute ideas and knowledge to students and students of Posiga High School and Milangodaa Village, Kec. Tomini Kab. South Bolaang Mongondow, North Sulawesi Province. The results showed that by holding socialization of the dangers of promiscuity students and students could realize and correct wrong behavior and find out other impacts that arise due to promiscuity.